Interaction of 2-deoxy-D-glucose and adenine with phosphate anion uptake in yeast - Kotyk, A (Folia microbiologica, 1992)
The transport of inorganic phosphate anions into yeast cells (after preincubation with glucose, fructose or another metabolizable sugar, and in the presence of glucose) shows two kinetic components with half-saturation constants of 40 mumol/L and 2.4 mmol/L. The uptake was strikingly stimulated by 2-deoxy-D-glucose (2-dGlc) at lower concentrations but inhibited above 100 mmol/L. A similar stimulation was caused by adenine (0.01-1 mmol/L) and a very small one by uracil and inorganic sulfate. It is suggested that either a phosphorylation reaction accompanies the transport (2-dGlc) or that some compounds stimulate the H(+)-ATPase more than inorganic phosphate itself and thus increase its rate of transport.
Keywords: kinetika; Deoxyglucose; Saccharomyces cerevisiae; Adenine; Ion Transport; Phosphates; Phosphorylation; fosforylace; adenin; iontový transport; fosfáty; deoxyglukosa; adenosintrifosfát; Adenosine Triphosphate; protonové ATPasy; Proton-Translocating ATPases; Kinetics